Honduras : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper looks at revenue mobilization efforts in Honduras. The country has made considerable progress over the last years, helping to stabilize its fiscal position. Although tax revenue collection ratios in Honduras are high, the statutory rates are aligned with regional peers. A formal benchmarking exercise supports the evidence pointing to Honduras's relatively good collection performance. The authorities' future revenue mobilization strategy should prioritize reforms aiming at increasing efficiency and compliance. The cost-benefit assessment of existing tax exemptions in terms of their policy objectives may offer guiding principles to prioritize reforms going forward. Compared to peers, statutory tax rates are similar and tax collection ratios are generally higher-a benchmarking exercise suggests that the current revenue envelope is close to its frontier. Going forward, there is a need to sustain revenue mobilization efforts, which will be instrumental to maintaining a sound fiscal position, reducing the infrastructure gap, and increasing social spending. Rationalizing large tax expenditures could contribute to these efforts.